Correlates of higher‐risk drug‐related behaviours at music festivals in New South Wales, Australia. (18th November 2021) - Healey, Amy; Siefried, Krista J.; Harrod, Mary Ellen; Franklin, Erica; Peacock, Amy; Barratt, Monica J.; Brett, Jonathan
Abstract: Introduction: There are few contemporary data on illicit drug use at music festivals. We describe drug use patterns and prevalence of specific higher‐risk drug‐related behaviours, and their associations with festivalgoer characteristics. Methods: We approached attendees at six major music festivals in New South Wales, Australia, from November 2019 to March 2020. Participants self‐completed an anonymous survey on prior and intended drug use and associated higher‐risk behaviours; double dropping; higher‐volume ethanol alongside drug use; higher quantity 3, 4‐methylenedioxymethamphetamine (MDMA); mixing stimulants; and preloading. Logistic regression and UpSet analyses were performed to identify festivalgoer characteristics and the intersection of high‐risk behaviours, respectively. Results: Of 1229 participants, 372 (30.3%) used or planned to use drugs at the festival. In multivariable analyses, men and those purchasing drugs both inside and outside the venue had greater odds of engaging in higher‐risk behaviours. Of those using MDMA, 47.9% reported double dropping. People using drugs for the first time had 3.3 (95% confidence interval 1.2–8.7) greater odds of higher‐volume ethanol alongside drug use. People reporting that police/police dog presence influenced their decision to take drugs had 2.2 (95% confidence interval 1.4–3.6) greater odds of preloading. In UpSet analysis, preloading was the most common intersection (17% of those using drugs). Discussions and Conclusions: Engagement in the five higher‐risk drug behaviours was common, particularly amongst males and those using drugs for the first time, while police/police dog presence appeared to influence higher‐risk behaviours amongst festival attendees. This information can be used to inform harm reduction advice, public health and law enforcement strategies.